2018
DOI: 10.1177/0886260518789144
|View full text |Cite
|
Sign up to set email alerts
|

Palestinian Adolescents’ Prolonged Exposure to Political Violence, Self- Esteem, and Post-Traumatic Stress Symptoms

Abstract: The goal of this study was to understand the relation between adolescents' long-term exposure to political violence (EPV) and post-traumatic stress symptoms (PTSS). We examined the relations among EPV, PTSS, and self-esteem to determine whether self-esteem could buffer the effects of EPV on PTSS. A systematic cluster random sample of 2,934 Palestinian adolescent boys and girls in the West Bank area of the Palestinian Authority and in East Jerusalem participated in a study using a self-administered questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Long-term exposure to political violence (EPV), such as the case of Israeli-Palestinian conflict, has led to profound physical and psychological distress to civilians [ 1 ], and results in the disruption of their social and economic structures [ 2 ]. Together and separately, these circumstances harm the mental health and development of children and youth [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term exposure to political violence (EPV), such as the case of Israeli-Palestinian conflict, has led to profound physical and psychological distress to civilians [ 1 ], and results in the disruption of their social and economic structures [ 2 ]. Together and separately, these circumstances harm the mental health and development of children and youth [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pervasive and long-standing Palestinian-Israeli conflict has exposed children and adolescents on both sides to PV [ 2 ]. The occupied Palestinian territories (oPt) (West Bank, East Jerusalem, and the Gaza Strip) were occupied by Israel in 1967, and has been the place of periods of significance escalations in violence since, including two major Palestinian uprisings (also called Intifadas ) against the occupation, first from 1987 to 1993 and then from 2000 to 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Past research and interventions in the context of armed conflict with child victims have reported that programs which focus on the promotion and generation of hopeful scenarios that promote mental health, self-esteem, self-efficacy, and active participation help to overcome the horrors of confrontation (Barry et al, 2013;Haj-Yahia et al, 2018;Schultz et al, 2012) and demonstrate minors' high capacities for resilience, empowerment, and posttraumatic growth.…”
Section: The Participatory Role Of Childrenmentioning
confidence: 99%
“…As previous investigations have reported, violations of human rights in childhood have a devastating effect because child survivors of atrocious acts are left with deep physical and emotional wounds that generate stress and trauma as well as affect their mental health and development (Fajardo Mayo et al, 2018;Haj-Yahia et al, 2018;Schultz et al, 2012;Wessells, 2016). Therefore, it is important and urgent that international communities, states, and governmental and nongovernmental institutions take practical measures aimed at the prevention of violence as well as the recovery of child victims or those in danger of becoming a victim of armed conflict to reduce the lifelong psychological and social problems associated with experiences of conflict and violence in childhood.…”
mentioning
confidence: 99%
See 1 more Smart Citation